Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The role of faculty members in promoting the culture of dialogue in the university environment from the point of view of students at the University of Hafr Al-BatinMrs. Budur Gasem Alshuraya2. The practice of primary school mathematics teachers of blended learning in the educational process in Dawadmi GovernorateMr. Saad Farhan Mohammed Al-Otaibi3. Teacher Professional Development in Light of the Saudi Vision 2030 and International ExperiencesMrs. Afnan Fayiz Awad Altalhy , Mrs. Afnan Omar Masoud , Mrs. Taghreed Abdu Homdi , Mrs. Faridah Rashid Alqithami , Mrs. Nora Abdulaziz Alharbi , Mrs. Dalal Mutlaq Alamrani , Mrs. Reem Khudher Alsaadi, Mrs. Maraam Misri Alutaybi4. Perceptions of social studies teachers about the role of strategic intelligence in supporting decision-making in pre-university education institutions and its impact on sustainable competitivenessMrs. Muna Rashid Al-Na'aimi5. The level of first year secondary students in the Kingdom of Saudi Arabia in critical speaking skillsProf. Mahmoud Helal Abdelkader6. Social support and its relationship to psychological well-being among tenth grade students in the governorates of GazaDr. Doaa Salim Ali Al-Kayal7. The level of Critical thinking of Mathematical students in Faculty of Education- Sana'a UniversityMrs. Bushra Abdalaleem Al-Usofi, Co-Prof. Dhekra Mohammed Al-baqeri8. The degree of Availability of the Global mathematics standards in the Geometry axis in the mathematics books of (1 st - 4th) grades, from the point of view of female teachers in the Sultanate of OmanDr. Mohammed Nassir Saif Alriyami
Keywords: Journal of Educational and Psychological Sciences